CS Education in the U.S.: Heading in the wrong direction? - Dewar, Robert (Communications of the ACM, 2009)
In this article the authors discusses methods used to teach fundamental principles of software engineering to students. The authors suggest that there exists the potential for a shortage of well-trained software engineers. Other topics include the knowledge required to build reliable systems that are both large and complex.